Panic Buying dalam Perspektif Islam: Studi Kasus Kelangkaan Minyak Goreng di Indonesia - Nila Saadati; Slamet Haryono (Universitas Batanghari Jambi, 2023)
This study aims to determine the law of punic buying in an Islamic perspective from a case study of scarcity of cooking oil in Indonesia. This research method is descriptive qualitative and social observation. The results of this study indicate that panic buying is a form of human behavior that has a psychological effect on abnormal conditions. Because in Islam, there is no concept of scarcity of natural resources, limited human ability to explore natural resources, and weak human faith and piety in efforts to develop the economy. Cooking oil purchasing behavior must be anticipated by developing a more efficient inventory and supply chain management strategy.